Absence of an intracellular cobalamin-binding protein in cultured fibroblasts from patients with defective synthesis of 5′-deoxyadenosylcobalamin and methylcobalamin - Rosenberg, Leon E. (1975)
Three distinct classes of human mutations (cbl A, cbl B, and cbl C) cause defective synthesis of cobalamin (Cbl; vitamin B(12)) coenzymes. Cultured fibroblasts from that unique class (cbl C) deficient in the synthesis of both Cbl coenzymes, 5′-deoxyadenosylcobalamin (AdoCbl) and methylcobalamin (MeCbl), were used to explore the underlying defect. We compared the uptake of transcobalamin II(TC II)-bound cyano[(57)Co]cobalamin (CN-Cbl) by cbl cells with that of other control and mutant cell lines. Although the cbl C cells initially took up CN-[(57)Co]Cbl normally, they were unable to retain it. To characterize this “leak” further, cell extracts were prepared following incubation and chromatographed on Sephadex G-150. After incubations of 1-2 hr, most of the CN-[(57)Co]Cbl accumulated by control cells was still bound to TC II; the remainder was free. Thereafter, an ever-increasing fraction of the labeled Cbl eluted with an intracellular cobalamin-binding protein (ICB); more than 80% of the total was so bound after 76 hr incubations. ICB had an apparent molecular weight similar to that of several Cbl “R” binders (about 120,000), but was distinguished from them by its failure to react with specific anti-“R”binder antiserum. Significantly, no ICB was detected in extracts of three different cbl C lines even aftr prolonged incubations, whereas its appearance in cbl A, cbl B, and mutase apoenzyme mutants was normal. We propose: that ICB is required for retention of cobalamins by cells; and that cbl C cells “leak” cobalamins and show defective synthesis of Cbl coenzymes because they lack this intracellular binder.